2023
DOI: 10.3390/polym15081884
|View full text |Cite
|
Sign up to set email alerts
|

Process Parameter Prediction for Fused Deposition Modeling Using Invertible Neural Networks

Abstract: Additive manufacturing has revolutionized prototyping and small-scale production in the past years. By creating parts layer by layer, a tool-less production technology is established, which allows for rapid adaption of the manufacturing process and customization of the product. However, the geometric freedom of the technologies comes with a large number of process parameters, especially in Fused Deposition Modeling (FDM), all of which influence the resulting part’s properties. Since those parameters show inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…For practical applications, it is necessary to further optimize the mechanical properties. Literature reports have revealed that proper adjustment in the input parameters (related to both machine and geometry) could lead to improvement in the properties of the FDM 3D prototypes. Thus, we believe that by regulating the interlayer angle of the printed TPU filaments through the FDM, continuous TPU porous scaffolds with different mechanical properties will be obtained, and thus, CNT/TPU CPCs with improved mechanical properties could be achieved, which has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For practical applications, it is necessary to further optimize the mechanical properties. Literature reports have revealed that proper adjustment in the input parameters (related to both machine and geometry) could lead to improvement in the properties of the FDM 3D prototypes. Thus, we believe that by regulating the interlayer angle of the printed TPU filaments through the FDM, continuous TPU porous scaffolds with different mechanical properties will be obtained, and thus, CNT/TPU CPCs with improved mechanical properties could be achieved, which has not been reported.…”
Section: Introductionmentioning
confidence: 99%